What happened to life expectancy in Spain in the 1980s?. Issue 5 (October 1997) - Chenet, L; McKee, M; Otero, A; Ausin, I
Abstract : BACKGROUND: Life expectancy at birth in Spain improved between 1972 and 1982, by 2.5 years for males and 3.2 years for females. This slowed considerably in the following decade, with increases of only 0.5 and 1.7 years respectively. OBJECTIVE: To determine the causes of death that have been responsible for the failure by Spain to maintain in the 1980s and 1990s the rate of improvement in life expectancy seen during the 1970s. DESIGN: Data from WHO mortality tapes grouped in a series of clinically meaningful categories were used to calculate the contribution of each category, in five year age groups, to the changing life expectancy at birth in the two periods. SETTING: Spain. RESULTS: The trend in life expectancy at birth in Spain over this 20 year period can be considered to have two components, both with important consequences for public health policy. Underlying trends include a steady negative contribution from respiratory cancer in men and a reduction in cardiovascular disease. More recent trends include a considerable deterioration in deaths among young adults, most notably from accidents and, possibly, AIDS. CONCLUSION: The failure to maintain the rate of earlier gains in life expectancy in Spain can be attributed largely to a few conditions, although these may indicate less obvious underlying problems. These findings have important consequences for prioritising public health policies.